THE RELATIONSHIP BETWEEN TEACHER TEACHING STYLE AND STUDENTS' LEARNING MOTIVATION IN LEARNING ENGLISH AT TENTH GRADE OF SMA NEGERI 1 SIANTAR PERUMNAS BATU VI - Gabriella Clarisa Silaban; Yanti Kristina Sinaga; Mungkap Mangapul Siahaan (RADJA PUBLIKA, 2025)
The purpose of this study is to write the relationship between teacher teaching styles and student learning benefits in the English division of class X of SMA Negeri 1 Siantar Perumnas Batu VI. This study is based on Grasha's (1996) teaching style theory, especially the facilitator teaching style, as well as the concept of learning motivation according to Sanchez-Boliver & Martinez-Martinez (2022) which emphasizes intrinsic motivation as a driver of student engagement. This study uses a quantitative descriptive correlational design. The study population was all class X students, while the sample was taken purposively from class X-2 which amounted to 36 students and 1 English teacher at SMA Negeri 1 Siantar Perumnas Batu VI. The research instrument was a questionnaire with a Likert scale, then the data were analyzed using the Person Product Moment correlation test through the SPSS program. The results of the study showed that there was a significant positive relationship between teacher teaching styles and student learning motivation with a correlation coefficient value of r = 0.537 and a significance of p = 0.000 (p <0.05). This indicates that the more appropriate the facilitator teaching style applied by the teacher, the higher the student's motivation in learning English. Researchers concluded that a facilitator's teaching style plays a crucial role in increasing student learning motivation. Therefore, teachers are advised to adopt a teaching style that focuses on student guidance, interaction, and independence to create a more engaging and motivating learning environment.